Editor’s Note - Pascual Espada, Jordán; González-Crespo, Rubén (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2020)
The International Journal of Interactive Multimedia and Artificial Intelligence provides an interdisciplinary forum in which scientists and professionals can share their research results and report new advances on Artificial Intelligence and Interactive Multimedia techniques. The research works presented in this issue are based on various topics of interest, among wich are included: AI for Software Engineering, Education, Computer Vision, Augmented Reality, Natural Language Understanding, Data Mining, Knowledge-Based/Expert Systems, Image Processing, Location systems, Internet of Things, Multiobjective Evolutionary Algorithms and Software architectures.
Keywords: Editors Note; IJIMAI